2018
DOI: 10.1177/0361198118801339
|View full text |Cite
|
Sign up to set email alerts
|

Three Methods for Anticipating and Understanding Uncertainty of Outputs from Transportation and Land Use Models

Abstract: This study demonstrates three methods for uncertainty propagation in transportation and land-use models (LUMs): Local Sensitivity Analysis with Interaction (LSAI), Monte Carlo (MC), and Bayesian Melding (BM). Two case-study settings are used to illustrate how these methods work, allowing for inter-method comparisons. LSAI can provide the sign of change implied by changes in model inputs, the relative importance of changes in different inputs, and a decomposition of changes in outputs due to the impact of input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…They found that the ranking of improvement projects may indeed be different if uncertainty is considered relative to treating all parameters and data as deterministic. Wang and Kockelman (2018) compared the strengths and weaknesses of three methods for uncertainty propagation in transportation and land-use models: Local Sensitivity Analysis with Interaction (LSAI), Monte Carlo (MC) methods, and Bayesian Melding (BM) method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that the ranking of improvement projects may indeed be different if uncertainty is considered relative to treating all parameters and data as deterministic. Wang and Kockelman (2018) compared the strengths and weaknesses of three methods for uncertainty propagation in transportation and land-use models: Local Sensitivity Analysis with Interaction (LSAI), Monte Carlo (MC) methods, and Bayesian Melding (BM) method.…”
Section: Literature Reviewmentioning
confidence: 99%